Identification of chloride intracellular channels as prognostic factors correlated with immune infiltration in hepatocellular carcinoma using bioinformatics analysis. Issue 45 (12th November 2021) - Huang, Juan-Jun; Lin, Jing; Chen, Xiaoli; Zhu, Wei
Abstract : Abstract: Chloride intracellular channel (CLIC) proteins are novel Cl-channels with 6 family members (CLIC1–6) that are known to play crucial roles in multiple physiological functions, such as neurological, cardiovascular, pulmonary, and auditory functions, and in various malignancies, including hepatocellular carcinoma (HCC). However, considerable challenges exist in identifying appropriate CLICs as therapeutic target molecules and prognostic biomarkers for HCC because the transformation of soluble or integral membrane protein forms, and specific pharmacological agents (agonists and antagonists) for distinct CLICs remains enigmatic. To address this issue and the possible molecular basis and the signaling networks activated by CLICs in HCC, we examined the transcriptional, promoter methylation, DNA mutation, survival, and immune infiltration data of CLICs in patients with HCC using the ONCOMINE, UALCAN, GEPIA, cBioPortal, and TIMER databases. The data showed that the expression levels of CLIC family members were differed between tumor and normal tissues. High expression levels of CLIC1 and CLIC3 were associated with advanced cancer stage in HCC patients. Low CLIC1 expression was associated with a better overall survival (OS). The DNA methylation levels of the CLIC1–3 and CLIC5–6 promoters in tumor tissue with HCC were significantly lower in HCC tissues than in normal tissues. Patients with CLIC1 alterations had a shorter OS than patients with unaltered CLIC1. Moreover, the expression levels of CLICs correlated with the infiltration of 6 different immune cells (B cells, CD4 + T cells, CD8 + T cells, neutrophils, macrophages, and dendritic cells). These results indicate that the increased mRNA expression and decreased promoter DNA methylation level of CLICs may play crucial roles in HCC tumorigenesis. The expression of CLIC family members was significantly correlated with the tumor immune status. High CLIC1 and CLIC3 expression levels could serve as biomarkers for identifying advanced-stage HCC. Moreover, a CLIC1 mutation rate of 18% was also observed and CLIC1 genetic alterations were significantly associated with lower OS in HCC patients. Abstract : Supplemental Digital Content is available in the text